WEB PORTAL USABILITY AMONG NIGERIAN UNIVERSITY STUDENTS: A CASE STUDY OF UNIVERSITY OF BENIN, NIGERIA (Nigerian Journal of Technology, 2014)
The web portal technology by Nigerian universities was adopted as a way to help curb one of the burdens of university’s principal managerial operations: “students’ academic management”. This study evaluates usability or "ease of use" of University of Benin (UNIBEN) web portal from the students’ holistic view through the four usability constructs (interface and information quality, system usefulness and overall satisfaction) of the developed Web Portal Usability Success (WEBPUS) Model. It  revealed that the informative features and usefulness of the web portal system has not encouraged students’ usability behaviour due to the portal’s inefficiencies to effectively  and satisfactorily achieve a range of specified or completed tasks irrespective of their competences in basic computer and internet capabilities.  http://dx.doi.org/10.4314/njt.v33i2.9